Helicobacter pylori infection and serum pepsinogen concentrations in an elderly population representative of Costa Rica - Une, Clas Allan (2022)
INTRODUCTION: Costa Rica has among the highest mortality rates from gastric cancer in the world, largely due to late detection. It is therefore important that economically and logistically sustainable screening is implemented in order to detect risk of developing cancer. We have previously shown that low pepsinogen (PG) values and infection with Helicobacter pylori-CagA+ are associated with risk of gastric atrophy and cancer in Costa Rican populations. OBJECTIVES: To determine how markers for gastric cancer risk are distributed in an elderly population representative of Costa Rica in order to design a screening strategy. METHODS: The population studied consists of 2,652 participants in a nationally representative survey of ageing. Information concerning epidemiologic, demographic, nutritional and life style factors is available. Serum PG concentrations as well as H. pylori and CagA status were determined by serology. Possible associations were determined by regression analyses. RESULTS: Antibodies to H. pylori were present in 72% of the population and of those, 58% were CagA positive. Infection with H. pylori was associated with higher PGI concentrations (p=0.000) and infection with H. pylori-CagA+ with lower PGI concentrations (p=0.025). Both showed association with lower PGI/PGII (p=0.006 and p=0.000). Higher age was associated with lower prevalence of H. pylori infection (OR=0.98; p=0.000) and CagA+ (OR=0.98; p=0.000) but not with PG values. Regions with high risk of gastric cancer showed lower PGI (p=0.004) and PGI/PGII values (p=0.021) as well as higher prevalence of H. pylori infection (OR=1.39; p=0.013) but not CagA+. Using cut-off values of PGI<100 μg/L and PGI/PGII<2.0, 2.5 and 3.0, 7-15% of the population would be considered at risk. CONCLUSIONS: H. pylori alone is not a useful marker for risk of gastric cancer. Screening using serum pepsinogen concentrations and infection with H. pylori-CagA+ is feasible in the general elderly population of Costa Rica but appropriate cut-off values have to be determined based on more clinical data and follow up capacity.